2017
DOI: 10.1126/science.aao0067
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “The complex effects of ocean acidification on the prominent N 2 -fixing cyanobacterium Trichodesmium

Abstract: Marine nitrogen--fixing cyanobacteria are important to the global carbon cycle and climate, as they provide vital new nitrogen supplies that allow phytoplankton to draw down atmospheric carbon dioxide (CO 2 ). Many experiments over the last decade have predicted that the globally--distributed tropical cyanobacterium Trichodesmium spp. will grow faster and fix 30--

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In a recent study, Hong et al (9) observed a significant decrease in growth and N 2 fixation rates under both replete (r750) and Fe-limited conditions at high CO 2 concentrations (750-Fe) relative to the controls, unlike this study and a number of other previous replete (3-6, 10, 25-28) and high-CO 2 /Fe-limited studies (5). Hong et al (9) attributed these discrepancies to ammonia contamination and metal toxicity in all other past studies, although ammonia was below the detection limit in our prepared Aquil medium and 25 M EDTA was added to control for metal toxicity (29). One central difference between this study and nearly all others relative to that of Hong et al (9) is that Trichodesmium cell lines were adapted (4-6) or acclimated (10,(26)(27)(28) to a low pH as a product of increasing CO 2 partial pressure on seawater carbonate chemistry similar to pH reductions in situ.…”
Section: Resultsmentioning
confidence: 74%
“…In a recent study, Hong et al (9) observed a significant decrease in growth and N 2 fixation rates under both replete (r750) and Fe-limited conditions at high CO 2 concentrations (750-Fe) relative to the controls, unlike this study and a number of other previous replete (3-6, 10, 25-28) and high-CO 2 /Fe-limited studies (5). Hong et al (9) attributed these discrepancies to ammonia contamination and metal toxicity in all other past studies, although ammonia was below the detection limit in our prepared Aquil medium and 25 M EDTA was added to control for metal toxicity (29). One central difference between this study and nearly all others relative to that of Hong et al (9) is that Trichodesmium cell lines were adapted (4-6) or acclimated (10,(26)(27)(28) to a low pH as a product of increasing CO 2 partial pressure on seawater carbonate chemistry similar to pH reductions in situ.…”
Section: Resultsmentioning
confidence: 74%
“…So our study reveals that coral species that highly depend on heterotrophy could, in the event of bleaching, rely not only on the supply of nutrients and energy from meso-macroplankton but also on a major supply of N by planktonic diazotrophs and picoplankton. Taking advantage of the consumption of planktonic diazotrophs or picoplankton that have developed on diazotrophy could be one of the main strategies for coral recovery facing bleaching, as both the activity and geographical distribution of diazotrophs will likely increase with future rising sea surface temperature (Breitbarth et al, 2007;Levitan et al, 2007;Hutchins et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an increase in sea surface stratification linked to sea surface warming, which tends to slow the nutrient supply to the surface, is projected for future oceans (Gattuso et al., ; Roy et al., ). Under these conditions, unpalatable N 2 ‐fixing Trichodesmium are especially favored, and their large blooms are expected to further expand under future global warming scenarios because enhanced N 2 fixation was found to persist under high CO 2 irrespective of phosphorus limitation (Hutchins & Fu, ; Hutchins et al., ; Walworth et al., ). Analogously to Nodularia blooms in the Baltic Sea (Wasmund, Nausch, & Voss, ), blooms of Trichodesmium in other marine systems develop seasonally in association with mixing of DIN‐depleted but phosphorus‐rich upwelling waters into warm, stratified oceanic waters that contain seed populations of Trichodesmium (Deutsch, Sarmiento, Sigman, Gruber, & Dunne, ; Hegde et al., ; Hood, Coles, & Capone, ).…”
Section: Discussionmentioning
confidence: 99%